Effects of skill and distance factors on center of mass and center of pressure during Golf putting - Park, J. S.; Lim, Y.-T.; Lee, J. W.; Kwon, M.-S. (Korean Journal of Sport Biomechanics, 2019)
Objective: The purpose of this study was to analyze the effects of skill and distance factors on CoP (Center of pressure) and CoM (Center of mass) during golf putting.